A Case Report on Generalised Muscle Spasms After Ornamental Tarantula Bites That Responded Well to Intravenous Calcium Gluconate Treatment - Ramesh, R.; Arulmoly, K.; Anushanth, U.; Aruna, G.; Suganthan, N. (Springer, 2023)
Here, we present a case of a 55-year-old male, who was admitted with a spider bite, which caused swelling of the hand and painful muscle spasms along with palpitations. The patient made a complete recovery after the administration of intravenous calcium gluconate, followed by oral calcium supplements. Although no specific treatment exists in Sri Lanka for spider bites, calcium supplements can be beneficial for Sri Lankan ornamental tarantula (Poecilotheria fasciata) bites.
Keywords: Calcium gluconate; Muscle spasms; Spider bite; Ornamental tarantula; Poecilotheria fasciata